Dissemination of household scale biodigester technology to produce biogas from animal waste - Abdul Mukhlis Ritonga; Masrukhi Masrukhi; Furqon Furqon (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
Diversification of energy use becomes a very important issue because of the decrease in the source of oil raw materials. Biogas is a renewable energy that can be used as an alternative fuel to replace fossil fuels such as kerosene and natural gas. Utilization of livestock waste to produce biogas can reduce commercial energy consumption such as gas and wood fuel. The purpose of this activity is to apply biogas technology and reduce the negative impact of pollution of cattle waste. The topography condition of Kalisalak village which is located in the highland area plus access location that is difficult to reach cause the gas fuel distribution process (LPG) is not optimal. Practicing skill by doing counseling and practice of making biogas digester and also performing assistance is very appropriate for the condition of Kalisalak Village community. The result of the dedication activity that 100% partners understand and able to make biogas digester. Five domestic digester units with volume 300 liter per unit are produced that can produce biogas from cow dung waste which can reduce the cost of gas fuel (LPG) by Rp. 23.000 every month, the environment is more awake from the smell of smell and greenhouse effect of cow dung waste pollution. With the application of biogas technology household scale is able to save the cost of the need for gas fuel, in addition to the more environmentally maintained hygiene.